2012
DOI: 10.1259/bjr/32750755
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of high-intensity focused ultrasound combined with transarterial chemoembolisation for hepatocellular carcinoma <5 cm: comparison with transarterial chemoembolisation monotherapy—preliminary observations

et al.

Abstract: Objective: To retrospectively compare the therapeutic effects of combined highintensity focused ultrasound (HIFU) and transarterial chemoembolisation (TACE) with TACE alone for the treatment of non-advanced hepatocellular carcinomas (HCCs) ,5 cm. Methods: We retrospectively reviewed the tumour responses of 32 HCCs of 25 patients who underwent combined HIFU and TACE, and 46 HCCs of 32 patients who underwent TACE only. The mean follow-up observation of the TACE+HIFU group was on average 31 months and that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Planned iatrogenic right hydrothorax with intra-pleural infusion of warm saline solution was reported in 272 cases, to enhance HIFU coupling in cases of liver dome tumor (26,35,36,38,41,45,52,55,75). Other studies reported on the use of artificial pleural infusion or artificial ascites in selected cases, without detailing the number of patients (42)(43)(44)49,51).…”
Section: Records Included For Qualitative Synthesis N=67mentioning
confidence: 99%
See 2 more Smart Citations
“…Planned iatrogenic right hydrothorax with intra-pleural infusion of warm saline solution was reported in 272 cases, to enhance HIFU coupling in cases of liver dome tumor (26,35,36,38,41,45,52,55,75). Other studies reported on the use of artificial pleural infusion or artificial ascites in selected cases, without detailing the number of patients (42)(43)(44)49,51).…”
Section: Records Included For Qualitative Synthesis N=67mentioning
confidence: 99%
“…Other studies reported on the use of artificial pleural infusion or artificial ascites in selected cases, without detailing the number of patients (42)(43)(44)49,51). Intragastric water filling and colon irrigation have also been described to optimize acoustic coupling and consequently reduce the risks of burn injuries to air-filled viscera that might interpose between the HIFU transducer and the target (41). The placement of degassed waterfilled balloons on the application site, with slight pressure to displace bowel and clear gas, is an additional mean to enhance the coupling and reduce the risk of injuries to innocent organs.…”
Section: Records Included For Qualitative Synthesis N=67mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported the use of IPI for ultrasoundguided HIFU ablation of liver tumors, although IPI was never the subject of these reports (11,12,18,19). Jung et al have described a delayed complication after IPI-assisted ultrasound-guided HIFU treatment of a liver tumor patient, a diaphragm rupture with herniation of the colon into the thoracic cavity (13).…”
Section: Discussionmentioning
confidence: 99%
“…Transcarterial chemoembolization (TACE) is a recognized preferable non-surgical treatment in this setting of paitents (Kim et al, 2012). In fact, 20%~50% of tumor tissue necrosis completely after TACE; even after repeated RESEARCH ARTICLE TACE, there are still cancer cells remaining, and the 5-year survival rate is only 9%~16.2% ( Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%